2019
DOI: 10.1021/acs.joc.9b01369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amino Terminal Clicked Dendrimers. Approaches to the Application as a Biomarker

Abstract: Herein, we present an easy and efficient synthesis of amino terminal dendrons, combining protection/ deprotection reactions with copper-catalyzed azide alkyne cycloaddition in a convergent way. This new approach affords dendrons in gram scale with excellent yields and easy purification. By choosing the appropriate azido-functionalized core, these dendrons lead to a more efficient and controlled convergent synthesis of dendrimers with different sizes and shapes and multivalence. The amino terminal dendrimers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In order to achieve a higher separation between amine terminal groups, 5-amino-2-(3-aminopropyl)pentanoic acid was selected as a platform to build the dendrimers. This will arrange the terminal amino groups in a 1,7 relative position, achieving less steric hindrance than in previously prepared BAPAD 21 or clicked dendrimers, 23 where the amino groups were in a 1,3 relative position. The presence of a carboxylic acid and two amino groups in the selected AB 2 monomer will ensure that all connections will be exclusively amide bonds.…”
Section: Synthesismentioning
confidence: 98%
See 2 more Smart Citations
“…In order to achieve a higher separation between amine terminal groups, 5-amino-2-(3-aminopropyl)pentanoic acid was selected as a platform to build the dendrimers. This will arrange the terminal amino groups in a 1,7 relative position, achieving less steric hindrance than in previously prepared BAPAD 21 or clicked dendrimers, 23 where the amino groups were in a 1,3 relative position. The presence of a carboxylic acid and two amino groups in the selected AB 2 monomer will ensure that all connections will be exclusively amide bonds.…”
Section: Synthesismentioning
confidence: 98%
“…However, as previously reported, characterization of dendrimers with high molecular weights and charges by MALDI-TOF is extremely difficult. 23,37,38 For G4-5 no MALDI spectrum could be obtained, probably due to the high lability of the Boc protecting groups (in Gx-NHBoc) and the high degree of positive charges (in G4-5) during measurements.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] After Tomalia's first report on poly(amidoamine) (PAMAM) dendrimers in 1985, 20 many research groups have reported the synthesis dendritic macromolecules using ether, ester, carbosilane, amide, and alkyne linkages. [21][22][23][24][25][26][27][28][29][30][31][32][33] Nevertheless, very few have reported the synthesis of dendrimers having urethane linkage. It is noteworthy that, as of now, SciFinder ® reveals less than 100 references showing the entry of polyurethane dendrimers, which is negligible as compared to the references reported on polyurethane polymers (more than 340,000).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] After Tomalia's first report on poly(amidoamine) (PAMAM) dendrimers in 1985, 20 many research groups have reported the synthesis dendritic macromolecules using ether, ester, carbosilane, amide, and alkyne linkages. [21][22][23][24][25][26][27][28][29][30][31][32][33] Nevertheless, very few have reported the synthesis of dendrimers having urethane linkage. It is noteworthy that, as of now, SciFinder ® reveals less than 100 references showing the entry of polyurethane dendrimers, which is negligible as compared to the references reported on polyurethane polymers (more than 340,000).…”
Section: Introductionmentioning
confidence: 99%